Nexus between tourism and ecological footprint in RCEP: Fresh evidence from Bayesian MCMC random-effects sampling - Nguyen Ngoc Thach; Bui Hoang Ngoc (Cogent Business & Management, 2023)
In recent years, environmental protection has been a priority goal in tourism policies worldwide, including the regional comprehensive economic partnership (RCEP). This study is conducted to explore the impact of tourism, economic growth, globalization, and human capital on environmental degradation in RCEP countries during 1995-2016. By adopting Bayesian random-effects regression to capture individual variations across countries, the findings show that tourism development improves environmental quality, while economic growth and globalization positively drive environmental degradation. The empirical result also finds that the influence of human capital on environmental damage is positive but not significant. These findings are expected to strengthen the belief of RCEP policymakers in promoting sustainable tourism.
Keywords: 650; Bayesian MCMC random-effects sampling; ecological footprint; economic growth; RCEP; sustainable tourism